Individual- and County-Level Religious Participation, Corporal Punishment, and Physical Abuse of Children: An Exploratory study. Issue 19 (October 2019) - Wolf, Jennifer Price; Kepple, Nancy Jo
Parental religiosity has been associated with corporal punishment. However, most of this research has focused exclusively on Christians and has not examined physical abuse. In addition, little is known about how the larger religious environment might be associated with discipline behaviors. In this exploratory study, we examine how individual- and county-level religious attendance are related to corporal punishment and physical abuse. We sampled and surveyed 3, 023 parents of children aged 12 and younger from 50 mid-sized California cities. We used weighted Poisson models to calculate the frequency of corporal punishment and physical abuse in the past year. Parents who attend religious groups used corporal punishment more frequently than parents who did not attend religious groups. However, those who lived in counties with greater rates of religious participation used corporal punishment less frequently than those living in counties with lower rates of religious participation. There were no effects for religious participation on physical abuse at the individual or county level. This exploratory study suggests that parents who attend religious groups may be more likely to use some types of physical discipline with children. Religious groups could be imparting parenting norms supporting corporal punishment at the individual level. More research examining specific doctrines and faiths is needed to validate the study findings.